Water hyacinth [Eichhornia Crassipes (Mart.)] invasion: implications for livelihoods in the central Rift Valley of Ethiopia - Gudina, Assefa; Woldemedhin, Dagne Getachew; Seyoum, Aseffa; Senbeta, Feyera; Assefa, Engdawork; Alemayehu, Afework (Frontiers in Sustainable Food Systems, 2025)
Water hyacinth spans extensive geographic areas in tropical and semi-tropical regions. Its impact on livelihoods is connected to the production of crops, fish, livestock, and other activities that influence costs and returns for rural smallholders. This invasive weed affects crop production by invading farmland adjacent to the lakes and has an impact on livestock by covering grazing land meant for animal feed. Although several studies have been conducted in Ethiopia, the livelihood impact of water hyacinth has been scarcely analyzed, quantified, and documented. This study evaluates the adverse effects of water hyacinth, particularly on crop production, livestock management, fish harvesting, and other off-farm incomes, by comparing groups of respondents’ proximity to Lake Koka and Demel in the Central Rift Valley of Ethiopia before and after a specified period. Data were collected from 348 sample households based on the nearness of farmlands to the lakes, both adjacent to (≤ 300 m) and distant from invaded lakes, six focus group discussions, six key informant interviews, and field observations to assess the impact using propensity scores, difference-in-differences, and weighted least squares methods. The result of difference-in-differences shows a decline in the total annual income by 823 ETB, income from crop production by 329 ETB per year, and income from off-farm activities by 6,952 ETB per year for those living adjacent to the invaded lakes. Although the impact varies according to the intensity of the water hyacinth infestation, it adversely affects rural livelihoods by reducing crop yields and returns from off-farm activities. The study did not find any significant impact on livestock production and harvested fish. Other control variables, such as education, experience, and interactions like dependency-age, experience-education, and land-lake, also influenced the impact of livelihood. As hypothesized, water hyacinth has caused differences in on-farm and off-farm incomes between groups of respondents. Further research is suggested to investigate the fish species favored and affected by this invasive weed. Ultimately, the impact of water hyacinth is of significant interest to affected communities, regional offices, policymakers, and scientists.